Losing Consciousness With John T. Warren. (April 2014) - Brower, Jay
In this article, I examine the experience of loss through a phenomenological description of disorientation based in lived experience. Drawing on the insights of queer theory, I explore disorientation as pathway to narrate death and dying in a way that breaks from linear historical frameworks of cultural meaning. Embedded in this conversation is also a call for a method of resuscitating and making visible the fragments of difference lived under erasure. My purpose is to grasp at what it means to mourn loss while embracing the attendant feelings that escape neatly established cultural systems. Thus, I ask how do we think through loss as an experience of disoriented-difference-made-abject?